Repair mechanism of Wuwei Fuzheng Yijing formula in di-2-ethylhexyl phthalate-induced sperm DNA fragmentation in mice - Chenming Zhang; Shiqi Wang; Zulong Wang; Qi Zhang; Rubing Chen; Hao Zhang; Zhong Hua; Sicheng Ma (Taylor & Francis Group, 2022)
Context Di-2-ethylhexyl phthalate (DEHP), a known persistent organic pollutant, can increase the sperm DNA fragmentation index (DFI).Objective To investigate the mechanism underlying the repair of DEHP-induced sperm DNA damage in mice by Wuwei Fuzheng Yijing (WFY) formula.Materials and methods The potential targets of WFY and sperm DNA fragment (SDF) were obtained from the TCMSP, BATMAN-TCM, OMIM and GeneCards. The protein-protein interaction (PPI) network, GO and KEGG pathway analyses of WFY-SDF were constructed. An animal model of DEHP-induced sperm DNA damage was replicated by gavage of SPF ICR (CD1) mice DEHP at 1 g/kg/d and treated with WFY at 8.92, 17.84 and 35.67 g/kg, respectively, for 60 d. Sperm DFI of each group was detected and compared. The target genes of WFY identified by transcriptomic and proteomic analyses were validated by qRT-PCR and Western blotting.Results Network pharmacology pathway analysis indicated that PI3K/Akt was the potential target of WFY on SDF. The DFI of the DEHP group (25.48%) was significantly higher than that of the control group (4.02%). The high-dose WFY group (19.05%) exhibited the most significant repairing effect. The related pathways were PI3K/Akt and metabolic. Aass, Aldh1a7, GSTA3, betaine homocysteine S-methyltransferase (Bhmt), Mug2 and Svs1 were screened and Bhmt was validated.Discussion and conclusions WFY can repair sperm DNA damage caused by DEHP, and the mechanism may be related to PI3K/Akt and metabolic pathways, and Bhmt. This provides a new direction for using traditional Chinese medicine to prevent and repair reproductive system injury caused by pollutants.